Implementasi Gaya Kepemimpinan Visioner Kepala Perpustakaan dalam Pengelolaan Perpustakaan Daerah Kabupaten Serdang Bedagai - Mickael Halomoan Harahap; Muslih Fathurrahman (Jurnal Pustaka Ilmiah)
The Regional Library of Serdang Bedagai Regency is experiencing dynamic development that requires visionary leadership to meet the demands of the times. This study aims to analyze the implementation and challenges faced by the Head of the Regional Library in applying a visionary leadership style. This research adopts a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. Data analysis was conducted using the Miles and Huberman model, which involves data reduction, data display, and conclusion drawing. The results indicate that the Head Librarian has successfully implemented a visionary leadership style in accordance with Robbins’ theory, which includes three main characteristics: a realistic vision, a credible vision, and an attractive vision. However, significant challenges remain, particularly the limited human resources who have not fully mastered information technology, as well as budget constraints. Nevertheless, the leader has been able to respond to these challenges with adaptive and collaborative strategies. This study concludes that visionary leadership plays an important role in transforming regional libraries into more modern, inclusive, and future-oriented institutions.